Role of Rituximab in the Treatment of Pemphigus Vulgaris: Patient Selection and Acceptability - Ciolfi C; Sernicola A; Alaibac M (Patient Preference and Adherence, 2022)
Christian Ciolfi *, Alvise Sernicola *, Mauro Alaibac Dermatology Unit, Department of Medicine (DIMED), University of Padua, Padua, Italy*These authors contributed equally to this workCorrespondence: Alvise Sernicola, Dermatology Unit, Department of Medicine (DIMED), University of Padua, Via Vincenzo Gallucci, 4, Padua, 35121, Italy, Tel/Fax +39 049 821 2924, Email alvise.sernicola@me.comAbstract: Anti-CD20 monoclonal antibody rituximab is an approved adjuvant treatment, in combination with oral corticosteroids, for patients with pemphigus vulgaris, a severe and potentially life-threatening autoimmune blistering skin disorder. Updated approaches to the management of pemphigus vulgaris support rituximab as a first-line adjuvant treatment to induce remission early in the course of disease; however, its feasibility in the clinical setting is often reduced by a series of limitations, including high cost of this biological drug, physician and patient concern for the risk of adverse reactions, and uncertainty regarding the optimum dosing and schedule of administration. The standard approved rituximab dosages, which are derived from lymphoma protocols, have been recognized to exceed the effective dose required for inducing B cell depletion, since the B cell burden in pemphigus vulgaris is much lower than in lymphoproliferative disorders. To overcome these limitations, recent research has investigated alternative regimens of rituximab, using lower doses of the drug. Moreover, differences in patient and disease characteristics that are highlighted in the literature strongly suggest that therapy should be tailored individually on a case-by-case basis: personalized treatment schedules may be necessary to optimize response to treatment and tolerability in different subjects, with the possibility of repeated infusions for severe forms and in case of relapse. Finally, low-dose regimens of rituximab were suggested to be favorable during the COVID-19 pandemic by providing a lesser degree of immune cell depletion while retaining a sufficient response. In conclusion, the current literature suggests that lower-dose regimens of rituximab are not only tolerable and cost-effective but may also be associated with a positive response in pemphigus vulgaris, comparable to that achieved with higher doses especially in early disease. Further evidence from rigorous clinical trials will be required to optimize lower-dose regimens of RTX and establish their position within the treatment scenario of pemphigus vulgaris.Keywords: pemphigus, rituximab, low dose, patient acceptability, treatment acceptability